Transcatheter aortic valve implantation for tricuspid aortic valve with a calcium bridge between the cusps: a case report - Nakashima, Masaki (Eur Heart J Case Rep, 2020)
BACKGROUND: Indications for transcatheter aortic valve (AV) implantation (TAVI) have been extended to patients with challenging anatomical features such as a bicuspid AV. However, no case reports of TAVI for tricuspid AV with a ‘calcium bridge’ have been published. CASE SUMMARY: We report the case of an 87-year-old woman with severe symptomatic aortic stenosis (AS). Pre-procedural multidetector computed tomography (MDCT) showed a calcium bridge between the non-coronary and left cusps. Although these cusps appeared to be fused together in the centre by the calcium bridge, the commissure area between the fused cusps appeared to normally open. We cracked apart the calcium bridge from the commissure area using balloon aortic valvuloplasty, which was guided by transoesophageal echocardiography. Subsequently, we successfully implanted a balloon-expandable transcatheter heart valve (THV). DISCUSSION: To our knowledge, this is the first report of TAVI for a tricuspid AV with a ‘calcium bridge’ between the non-coronary and left cusps. In our patient, the unique structure of cusp fusing in the centre seemed to be caused by an acquired atherosclerotic process, as documented using a contemporary technique, i.e. MDCT. Cracking the calcium bridge with a balloon aortic valvuloplasty ensured that the THV adequately expanded. Severe AS caused by a calcium bridge may be treated with detailed evaluation of the AV morphology together with a procedural strategy planning.